Evaluation of Horizontal Shear Performance of Composite Girders Using Separable Shear Connectors - Dae-Sung Jung; Se-Hyun Park; Jong-Wook Han; Chul-Young Kim (Applied Sciences)
The increased volume of heavy vehicles and use of de-icing agents on concrete bridge decks accelerates the deterioration of these structures. Therefore, the rapid replacement of these structures has attracted considerable attention, with prefabricated bridges being the preferred option. Conventionally, horizontal shear connections between girders and precast decks have incorporated rebar stirrup shear connectors. Although effective for initial construction, this method renders dismantling of aged decks complex, because rebar connectors are fully embedded within girders. This study introduced an embedded separable shear connector that minimizes deck-breaking and facilitates easy reinstallation by the simple separation of the deck from the girder. Horizontal shear and flexural tests on composite girders and comparisons with various design codes were conducted to evaluate this connector. The results of horizontal shear tests confirmed that securing sufficient embedment depth is necessary to prevent the pull-out failure of shear connectors. Additionally, prestressed concrete composite girder flexural tests with improved design verified that the detachable shear connectors exhibited an approximately 60% improvement in flexural performance compared with conventional reinforcement shear connectors.